Analytical Study of Hadiths about Women as Source of Slander - Mayada, Wafiq; Munandar, Munandar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The word slander is often spoken in society in everyday life, namely defamation. But in this study, the word slander in question is a trial for women and men. It is said in a hadith of the Prophet Muhammad. "I have not left behind a slander for humans which is more dangerous for men than (its slander) for women." Regarding this hadith, many people still understand it textually without looking at the content of the related hadith. Perceptions like this fall are accompanied by attitudes of blaming and defaming women. Therefore, the understanding of women's hadith as slander cannot be understood in general but must be understood by looking at the asbab al-wurud or fiqh al-hadith of the hadith. Because if you understand it just by looking at the hadith, women are indeed a dangerous source of slander for men, where a woman can be said to be slanderous if she cannot protect herself from things that are prohibited in Islam. This hadith is also considered valid. In this research, the author will discuss the analysis of the targeted hadith and what the scholars think about this hadith, which aims to increase knowledge, understanding, and insight for writers and readers in understanding hadiths, especially women, as slanderers. The method used by the author refers to the tahlili (analytical)/qualitative method in the form of library research.